PERENCANAAN GEDUNG RUMAH SAKIT NYITDAHTABANAN MENGGUNAKAN STRUKTUR BAJA DENGAN SISTEM RANGKA BREISING DAN TANPA BREISING - I Made Wika Darmawan; Putu Aryastana; I Made Ardantha (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT Nyitdah Hospital Building - Tabanan is planned to use steel structure by utilizing skeleton brace system and without brace. This planning is done to find out the comparison of dimensions that occur when a Steel Structure in the add framework brace. The steel structure of this Hospital is based on SNI 1729 - 2015 Specifications for structural steel building buildings. The method used in this planning is using Load Resistance Factor Design (LRFD) method. The LRFD method is a method of planning by means of nominal capacity to anticipate uncertainties in the material used, while with the resistance factor to anticipate uncertainty in the variation of work load. The loads that work on the structure of the Hospital Building, calculated and analyzed the results obtained that the steel structure without brace experiencing a large shear force. The shear force occurs greatest in the beam with a ratio of 89.7% of the allowable shear force. After added brace framework, is brace type X and V inverted obtained a decrease of shear force. For brace type X shear forces that can be retained up to 30.65% of the shear force of the structure without brace. And for inverted breeding V can hold up to 21.33%, preferably 9.32% of brace type X. But the force that occurs not only sliding, the beam occurs moment and the column is pressed. In this case the type X breeders can withstand both the moment force on the beam and the compression force in the column, while the breed of type V is reversed, the moment that occurs on the beam becomes large. Brace Type X was chosen for the redesign of Nyitdah Hospital Building - Tabanan by considering the dimensions used in bias smaller than the structure without brace. The shear, moment and tap forces that occur in the structure can already be retained by the main structural frame and additionally the type X brace frame. Key word: steel, brace, LRFD